To simplify the expression \( 17x + 10 - 3(2x + 1) \), we will follow these steps:
-
Distribute the -3 to the terms inside the parentheses: \[ -3(2x + 1) = -3 \cdot 2x - 3 \cdot 1 = -6x - 3 \]
-
Substitute this back into the original expression: \[ 17x + 10 - 6x - 3 \]
-
Combine like terms:
- Combine the \( x \) terms: \( 17x - 6x = 11x \)
- Combine the constant terms: \( 10 - 3 = 7 \)
Putting it all together, we get: \[ 11x + 7 \]
Thus, the expression \( 17x + 10 - 3(2x + 1) \) simplifies to \( 11x + 7 \).
The equivalent expression is 11x + 7.